Hubungan Peran Orangtua dan Cara Berpakaian Wanita dengan Pencegahan Pelecehan Seksual - Liwa Ushidq; Sarah Zahirah; Fatma Tresno Ingtyas; Laurena Ginting (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The prevention of sexual harassment among students is a major challenge that requires a holistic approach, involving an understanding of power dynamics, social norms, and clear, firm campus policies. Several theories can be used to develop effective strategies in preventing sexual harassment among students. This study aims to explore the relationship between the role of parents and women's clothing choices in the prevention of sexual harassment. The method used in this study is quantitative analysis, involving 52 respondents. Data were collected through questionnaires measuring the variables of parental role, women's clothing, and sexual harassment prevention. This research uses both descriptive and quantitative research types.The results of the descriptive analysis show that the average score for parental role is 35.87, women's clothing is 33.42, and sexual harassment prevention is 35.31. The findings of this study emphasize the importance of the role of parents in educating their children about safe clothing choices and behaviors that help prevent sexual harassment. This research is expected to contribute to efforts in preventing sexual harassment through education and public awareness.